An Overview of the Recent Progress in Polymeric Carbon Nitride Based Photocatalysis. Issue 7 (22nd April 2021) - Humayun, Muhammad; Ullah, Habib; Tahir, Asif Ali; bin Mohd Yusoff, Abd. Rashid; Mat Teridi, Mohd Asri; Nazeeruddin, Mohammad Khaja; Luo, Wei
Abstract: Recently, polymeric carbon nitride (g‐C3 N4 ) as a proficient photo‐catalyst has been effectively employed in photocatalysis for energy conversion, storage, and pollutants degradation due to its low cost, robustness, and environmentally friendly nature. The critical review summarized the recent development, fundamentals, nanostructures design, advantages, and challenges of g‐C3 N4 (CN), as potential future photoactive material. The review also discusses the latest information on the improvement of CN‐based heterojunctions including Type‐II, Z‐scheme, metal/CN Schottky junctions, noble metal@CN, graphene@CN, carbon nanotubes (CNTs)@CN, metal‐organic frameworks (MOFs)/CN, layered double hydroxides (LDH)/CN heterojunctions and CN‐based heterostructures for H2 production from H2 O, CO2 conversion and pollutants degradation in detail. The optical absorption, electronic behavior, charge separation and transfer, and bandgap alignment of CN‐based heterojunctions are discussed elaborately. The correlations between CN‐based heterostructures and photocatalytic activities are described excessively. Besides, the prospects of CN‐based heterostructures for energy production, storage, and pollutants degradation are discussed. Abstract : Graphitic carbon nitride (g‐C3 N4 ) as a promising visible‐light photocatalyst has broad applications in solar energy conversion and environmental remediation owing to its low cost, robust and environmental friendly nature. In this critical review, we highlight the recent development, fundamentals, nanostructures design, advantages and challenges of g‐C3 N4 . Further, we highlight the latest information on the improvement of CN‐based heterojunctions.